Freedom of Expression on Social Media in Indonesia: Why are the limitations imposed? - Eka Wisanjaya, I Gede Pasek; Rosy Widodo, Putri Bella (Udayana Journal of Law and Culture, 2024)
As part of the fundamental human rights, the right to freedom of expression is neither absolute nor unlimited; there are limitations on exercising this right in the context of the democratic rule of law. Presently, the exercise of the right to freedom of expression in social media has been misused by the emergence of fake news or information (hoaxes). The limitations to exercising the right, as stipulated under the Indonesian national laws such as the 1945 Constitution of the Republic of Indonesia , Law No. 12 of 2005 concerning the Ratification of the International Covenant on Civil and Political Rights, Law No. 39 of 1999 concerning Human Rights, and Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions , are aimed at respecting and protecting the dignity of individuals or other people and protecting the public interest and national security. This article aims to discuss the impact of entities outside Indonesian sovereignty on implementing legal norms limiting the exercise of the right to freedom of expression in social media and the implementation of the norms under Indonesian national law. The method used is normative legal research using a statutory, case, and fact approach. The analysis shows that limitations on exercising the right to freedom of expression on social media under Indonesia’s national sovereignty have not been efficient due to the entities of social media platforms outside the territory of Indonesia, which may not be entirely located or subject to the scope of national jurisdiction.